1969
DOI: 10.1063/1.1670783
|View full text |Cite|
|
Sign up to set email alerts
|

Vibronic Effects in Photochemistry—Competition between Internal Conversion and Photochemistry

Abstract: An emission spectroscopic investigation was carried out on molecules capable of undergoing photochemistry as well as on those that cannot. Where photochemistry does occur, the quantum yield of fluorescence (φF) depends upon the particular vibrational level excited within a vibrational manifold of an excited electronic state. That is, φF generally decreases with excitation into successively higher vibrational levels. The mechanism responsible for these results involves competition between internal conversion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
2

Year Published

1969
1969
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 14 publications
2
54
0
2
Order By: Relevance
“…It was previously shown that certain naphthopyrans exhibit decreased fluorescence and/or increased photochemistry when upper vibrational levels within S 1 are excited, [18][19][20][21][22] whereas for molecules not showing photochemistry the fluorescence quantum yield was independent of the exciting wavelength. [18] It has also been demonstrated, by a kinetic/thermodynamic approach, that the ring-opening reaction is an extremely fast process and therefore can compete with vibrational relaxation.…”
Section: Wavelength Dependence Of Fluorescence and Photochemistrymentioning
confidence: 98%
“…It was previously shown that certain naphthopyrans exhibit decreased fluorescence and/or increased photochemistry when upper vibrational levels within S 1 are excited, [18][19][20][21][22] whereas for molecules not showing photochemistry the fluorescence quantum yield was independent of the exciting wavelength. [18] It has also been demonstrated, by a kinetic/thermodynamic approach, that the ring-opening reaction is an extremely fast process and therefore can compete with vibrational relaxation.…”
Section: Wavelength Dependence Of Fluorescence and Photochemistrymentioning
confidence: 98%
“…This shows that some of the energy delivered by the photon in excess of that needed for a purely electronic excitation (0-0 transition) is not lost as heat until after it has been utilized for motion across the small barrier separating the minimum at the initial geometry from the product side. Such extremely rapid photochemical processes, capable of competing with thermal deactivation in condensed media, have been described previously (Becker et a/., 1969), but this appears to be the first case in which one can be sure that the whole process involves only the singlet manifold (the molecule is still in the singlet state after the escape since it fluoresces at the end). In the previous reported cases, involvement of intersystem crossing was unlikely but hard to exclude with certainty.…”
Section: (B) Electrocyclic Ring Opening In Dewar Aromaticsmentioning
confidence: 99%
“…[1][2][3] Chromenes, a class of photochromic compounds, have been studied in their photochromic properties in the pioneering work by Becker et al more than 30 years ago. [4][5][6][7][8][9][10][11] Naphthopyran is a chromene derivative (benzochromene) and can be divided into three isomers, 3H-naphtho [2,1-b]pyrans, 2H-naphtho [1,2-b]pyrans, and 2H-naphtho [2,3-b]pyrans (Scheme 1). The photochemistry and photophysics of 3H-naphtho [2,1-b]pyrans were extensively studied.…”
Section: Introductionmentioning
confidence: 99%